Kepemimpinan Transformatif Yesus Kristus: Tinjauan Teologis dan Eklesiologis - Rawung, Tommy; Tanugraha, Yoas; Kriswibowo, Arimurti (Jurnal Teologi Pambelum, 2025)
This study aims to explore and understand Jesus' transformative leadership style from an ecclesiological and theological perspective. The research employs a qualitative methodology based on a literature review, focusing on four key aspects: theological context, ecclesiological context, application in public and business sectors, and its impact on faith development. The findings indicate that Jesus' leadership is not merely a historical model but a relevant and applicable framework for contemporary leadership contexts. His leadership is confirmed as servant-oriented, influential, and transformative, providing guidance for leaders seeking to integrate ethical principles and effectiveness into their leadership practices. This model remains pertinent and adaptable across various modern leadership settings, offering an alternative to authoritative approaches by emphasizing empathy, service, and individual development. This study makes a significant contribution to the understanding of Jesus' leadership, exploring how His transformative leadership principles can be applied and integrated into contemporary leadership practices.